Determinación de valores hematológicos de ganado de lidia, en la “hacienda La Cristalina” ubicada en el cantón Guaranda, provincia Bolívar - Barragán Taco, Edison Macgyver (2018)
The determination of hematological values of cattle of Lidia, in the "Hacienda the crystalline" located in the canton Guaranda, province Bolivar whose objectives: to determine the hematological values of cattle of Lidia and to be compared with studies carried out in other countries. The methodology was to take blood samples of the coccygeal vein in 100 bovines of Lidia in different age, color, sex, body condition and send to the laboratory to be analyzed in the automatic hematology equipment. We found 94 samples suitable for establishing blood count values with normal distribution, Red blood cells 5.5 – 8.6 106/Μ L; Hemoglobin 110 – 143 g/L; Hematocrit 32.3 – 41.7%; Volume Corpuscular Medium 47 − 62 FL; Hemoglobin corpuscular mean 15.7 − 20.7 pg; Hemoglobin concentration corpuscular mean 306 – 382 g/L; White blood Cells 6.0 – 12.9 x 103/Μ L; Lymphocytes 4.2 − 10.0 × 103/Μ l; monocytes 0.2 − 0.9 × 103/Μ l; Neutrophils 0.1 – 2.9 × 103/Μ l; Eosinophils 0.1 – 1.8 × 103/Μ L and basophils 0.0 – 0.2 × 103/Μ l; Lymphocytes 59.6 – 90.3%; Monocytes 2.8 – 9.1%; Neutrophils 1.2 – 28.7%; Eosinophils 1.4 – 12.8%; Basophils 0.1 – 1.5%; Platelets 80.6 – 368.1 × 103/Μ L.The results were compared with international bibliographic references and found differences in corpuscular hemoglobin, lymphocytes, neutrophils and platelets with the study of Fox et al. (2002), Escobar (2008), Gasque (2008); And, Frandson (2009).